2015
DOI: 10.1007/s10646-015-1599-1
|View full text |Cite
|
Sign up to set email alerts
|

Patchy sediment contamination scenario and the habitat selection by an estuarine mudsnail

Abstract: Since mudsnails are able to avoid contaminated sediment and that the contaminants in sediment are not uniformly distributed, the mudsnail Peringia ulvae was exposed to cadmium (Cd) spiked sediment and assessed for avoidance response in a heterogeneous contamination scenario. Four Cd concentrations were prepared and disposed in patches on dishes, which were divided in 25 fields (six fields for each sediment concentration); 24 organisms were deployed in the central field, with no sediment. Observations were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…These authors observed that among the different lineages tested, the sensitivity and early reactiveness of the organisms to avoid copper was directly related to the lethal sensitivity of the lineages. Other invertebrates such as the cladoceran D. magna (exposed to pulp mill effluents [53]; atrazine [51]; and salinity as stress factor [54]), the freshwater copepod Boeckella occidentalis intermedia (crude oil as the contaminant [55]), the ostracod Heterocypris incongruens (salinity as the stress factor [54]), the gastropod Peringia ulvae (sediment spiked with cadmium [56]), the freshwater shrimp Atyaephyra desmarestii (exposure to copper [39,[57][58][59]), the marine shrimp Litopenaeus vannamei (exposed to copper [60,61]), and the saltmarsh shrimp Palaemon varians (exposed to musks and sunscreens [25,62]) have been tested for avoidance. In general, the avoidance response reported in those studies was more sensitive than the lethal and some sub-lethal endpoints described by other authors (see references cited above).…”
Section: Avoidance: a Repellency-driven Behavioral Responsementioning
confidence: 99%
“…These authors observed that among the different lineages tested, the sensitivity and early reactiveness of the organisms to avoid copper was directly related to the lethal sensitivity of the lineages. Other invertebrates such as the cladoceran D. magna (exposed to pulp mill effluents [53]; atrazine [51]; and salinity as stress factor [54]), the freshwater copepod Boeckella occidentalis intermedia (crude oil as the contaminant [55]), the ostracod Heterocypris incongruens (salinity as the stress factor [54]), the gastropod Peringia ulvae (sediment spiked with cadmium [56]), the freshwater shrimp Atyaephyra desmarestii (exposure to copper [39,[57][58][59]), the marine shrimp Litopenaeus vannamei (exposed to copper [60,61]), and the saltmarsh shrimp Palaemon varians (exposed to musks and sunscreens [25,62]) have been tested for avoidance. In general, the avoidance response reported in those studies was more sensitive than the lethal and some sub-lethal endpoints described by other authors (see references cited above).…”
Section: Avoidance: a Repellency-driven Behavioral Responsementioning
confidence: 99%
“…Deforestation and habitat fragmentation can also enhance soil erosion and leaching of mercury (Hg), becoming an important source of contamination to watersheds and aquatic life (Mainville et al, 2006;Roulet et al, 1999). Contaminants can also potentially act as chemical barriers in ecological systems, reducing the connectivity of the landscape even at lower concentrations (Araújo et al, 2016(Araújo et al, , 2018. For instance, Poecilia reticulata fishes avoided crossing waters contaminated with the herbicide atrazine, which can lead to isolation of populations and habitat fragmentation (Araújo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, contaminants can potentially affect organism movement and dispersion in the landscape. For instance, nonlethal concentrations of different classes of contaminants can affect speed, grazing (Bernot et al, 2005), habitat selection (Araújo et al, 2016; McCloskey & Newman, 1995), path tortuosity (i.e., how straight a path is; Kane et al, 2004), and predator avoidance (Zhou & Weis, 1999). Changes in these behaviors could further reduce animal movement and functional connectivity of the landscape and consequently worsen the effects of fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that contaminants can also be hazardous by triggering escape behavior (spatial avoidance) or preventing the preference for a habitat in recolonization processes (Lopes et al 2004;De Lange et al 2006;Rosa et al 2012;Ara ujo et al 2016c). The nonforced exposure approach simulates the different scenarios of spatial distribution of the contaminants that can potentially be observed in the field, either as a contamination gradient or a patchy distribution (Ara ujo et al 2016b). The approach using a nonforced exposure scenario (organisms are not confined to only one concentration/sample, but instead they can choose to stay in different ones) is a way of checking how organisms' displacement and habitat-selection processes are affected by contamination.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the use of avoidance and preference in a nonforced exposure system is an alternative and complementary approach in ecotoxicology that has shown its usefulness in contamination-driven habitat-selection studies (Ara ujo et al 2016c. The nonforced exposure approach simulates the different scenarios of spatial distribution of the contaminants that can potentially be observed in the field, either as a contamination gradient or a patchy distribution (Ara ujo et al 2016b). To simulate those scenarios, organisms are simultaneously exposed to different environmental samples or concentrations of toxicants in a free-choice, multicompartmented, nonforced system, allowing them to move toward the most favorable zones (Lopes et al 2004;Moreira-Santos et al 2008).…”
Section: Introductionmentioning
confidence: 99%